DIGITAL DENTISTRY AS A NEW CULTURE OF LEARNING AND PRACTICE - Padilla-Avalos, César-Augusto (2025)
Dentistry has experienced a profound digital transformation in recent years. Each year brings new technological advances, and keeping pace with them can be a demanding task. Three-dimensional workflows, digital scanners, and CAD/CAM (Computer-Aided design and manufacturing) systems are now part of daily clinical reality. However, the true challenge is not only to adopt new tools but to educate professionals capable of critical thinking and sound decision-making. Diagnosis, planning, and daily practice have also evolved. Today, digital systems play a central role in education because they allow students to practice procedures before treating real patients (1). Reports from the FDI World Dental Federation and the World Health Organization highlight that digital transformation is more than a technical change; it represents a new way of understanding access and equity in modern dentistry (2,3).